Analisis Faktor Yang Mempengaruhi Perilaku Pencegahan DBD Di Wilayah Kerja Puskesmas Tembilahan Kota - Yulistia, Yulistia; Mitra, Mitra; Muryanto, Irwan (Yayasan Jompa Research and Development, 2025)
Efforts to prevent dengue fever (DBD) are essential for breaking the transmission chain of the disease. According to the WHO, there are approximately 100-400 million cases of dengue infection worldwide each year. In Indonesia, the cumulative case fatality rate (CFR) from January to December 2022 was 0.90%. In Riau, the CFR increased to 0.8%, representing a 128% rise compared to the previous year. In Indragiri Hilir, there were 157 cases and four fatalities due to DBD throughout 2023, with the highest incidence occurring in Puskesmas Tembilahan Kota, which reported a CFR of 6%. This study was to identify factors associated with DBD prevention efforts. A quantitative analytical observational study with a cross-sectional design was conducted. The population consisted of 11,130 households in the working area of Puskesmas Tembilahan Kota, with a sample of 172 respondents from the Tembilahan Kota and Pekan Arba sub-districts. Sampling was performed using proportional and simple random sampling techniques. Data analysis included univariate analysis to assess data proportions, bivariate analysis using the chi-square test, and multivariate analysis through multiple logistic regression. The results revealed that 55.8% of respondents did not engage in DBD prevention efforts. Significant associated variables included knowledge (POR 4.259), attitudes (POR 4.377), and the role of health workers (POR 11.290), with the dominant variable being the role of health workers.